Survey on Fault Detection and Diagnosis Using Neural Network in WBAN - N.S.Kalpana, R; P.Nallathai, Dr (International Journal of Engineering and Technology, 2018)
Wireless Body Area Networks (WBAN) is the sensor network used for monitoring health information in e-health systems. WBAN is a combination of sensors used to obtain vital information from the body. It is a special type of WSN. WBAN technology should handle the data in a smart way by reacting to the monitored data and to evaluate the data.Â ItÂ requiresÂ fault detection and diagnosis methods for sensors used in WBAN.Â This paper gives a survey of different types of neural-network approaches for faults detection and diagnosis in WBAN using neural network.Â Â